Associations between burnout symptoms and social behaviour: exploring the role of acute stress and vagal function - Wekenborg, Magdalena Katharina; Hill, LaBarron K.; Grabbe, Pia; Thayer, Julian F.; Kirschbaum, Clemens; Lindenlaub, Susan; Wittling, Ralf Arne; Dawans, Bernadette von (BMC public health, 2022)
The study aimed to investigate the link between burnout symptoms and prosocial behaviour, as well as the role of acute stress and vagally-mediated heart rate variability (vmHRV) on this association.